Subacute thyroiditis following COVID19 vaccine: Report of four cases - El Ghandour, Sara; Al Ghazal, Nisrine (Journal of Diabetes and Endocrine Practice, 2021)
An increase in the incidence of subacute thyroiditis (SAT) following the COVID-19 vaccine. The aim of this report is to shed the light on different presentations of SAT postCOVID-19 vaccine while reviewing the link between the vaccine and subsequent thyroid inflammation. We present the case of a middle-aged man who presented symptoms of SAT 1-week postvaccine. He achieved euthyroidism 6 weeks later. We also present the case of a middle-aged woman with less severe symptoms of SAT 4 weeks after the vaccine. She is in the hypothyroid phase 11 weeks later. A 37-year-old male developed severe symptoms 2 weeks after the first dose and is still hyperthyroid 5 weeks later. A 36-year-old woman presented with silent SAT 3 weeks after the first dose. Cases of SAT following SARS-Cov-2 are now reported increasingly. COVID-19 can cause thyroiditis via direct cell, or alternatively though immune destruction of the thyroid in genetically susceptible individuals. Similarly, the vaccine can promote inflammation through the same mechanisms. Indeed, there is a postulated cross-reactivity between the spike protein and thyroid antigens. More-so, there is the studied vaccine adjuvant effect on the endocrine system, namely the thyroid in this case. Cases of SAT postCOVID-19 vaccines are increasingly reported. Theories are similar to COVID19-induced thyroiditis but also other mechanisms are uniquely mediated by vaccines. A low threshold should be set to diagnose SAT in patients with one or more hyperthyroid symptoms presenting 1–8 weeks postCOVID-19 vaccine.
Keywords: COVID-19; COVID-19 vaccination; subacute thyroiditis; thyroid; thyroiditis